Supramolecular complexation of C60 and C70 by helical nanographene incorporating N-heterotriangulene and hexabenzocoronene subunits - Kinzelmann, Marina; Fröhlich, Nina; Gnannt, Frederik; Borstelmann, Jan; Frühwald, Stefan; Oleszak, Christoph; Jux, Norbert; Görling, Andreas; Kivala, Milan; Drewello, Thomas (RSC Advances, 2025)
Supramolecular host-guest complexes are studied in the gas-phase evaluating a new host molecule for fullerenes (C60 and C70). The new host molecule is a double N-heterotriangulene-[5]helicene (NTH), consisting of two N-heterotriangulene (N-HTA) blades embedded into a hexabenzocoronene-like backbone with helically curved topology. Host-guest complexes of [1:1]+˙/2+, [1:2]+˙/2+, [2:1]2+ and [2:3]2+ stoichiometry and charge state are formed by electrospray ionization-mass spectrometry (ESI-MS). Ion formation occurs through electrochemical oxidation of the N-HTA moieties. Energy-resolved collision-induced dissociation (ER-CID) experiments reveal the noncovalent binding of the fullerenes to the NTH molecule and provide an order of stability for the complexes. Density-functional theory (DFT) calculations establish the lowest energy geometries of the complexes.
Gesehen am 24.07.2025